Public Health Insights into Cardiovascular Risks among Diabetic Patients: Evaluating the Individual and Combined Effects of Amlodipine and Metformin - Watt, James; Zahidullah; Sandhu, Ali Raza; Abowath, Misbah Zakir; Alamgir, Aisha (Indus Journal of Bioscience Research, 2025)
Background: Diabetes patients are more susceptible to cardiovascular disease (CVD), hence lowering the risk factors linked with CVD requires effective treatment techniques. Objective: To evaluate the individual and combined effects of Amlodipine and Metformin on cardiovascular risks in diabetic patients. Methodology: A prospective randomized, double-blind cohort study was conducted at three hospitals in Pakistan, enrolling 1,386 adults with type 2 diabetes over two years. Three groups of participants were randomly assigned to receive either amlodipine, metformin, or both. The dosages were modified in accordance with the clinical response, and blood pressure, glycemic control, and cardiovascular risk indicators were observed at regular intervals of 3, 6, 12, 18, and 24 months. SPSS version 26 was used to analyze the data. The three groups were compared for differences in cardiovascular risk using comparative analyses (t-tests). A significant threshold of p < 0.05 was established. Results: When it came to cardiovascular risk indicators, the Combination group outperformed the Amlodipine and Metformin groups by a substantial margin at 24 months. With statistically significant p-values (p=0.004, p=0.015), the decreases in systolic blood pressure (130.03 mmHg) were more marked than those in the Amlodipine (132.63 mmHg) and Metformin (132.13 mmHg) groups. Additionally, the Combination group had the lowest Hemoglobin A1c (HbA1c) values, 5.81 ± 0.51; this suggests better glycemic management. Moreover, significant enhancements in lipid profiles and decreases in fasting blood glucose levels were seen. Conclusion: The combination of Amlodipine and Metformin provides superior cardiovascular protection in diabetic patients, highlighting the importance of dual therapy in managing cardiovascular risks associated with diabetes.